Comparative behavior of input cost and output prices of selected crops of Gujarat - Devi, Ganga; Zala, Y.C. (Annals of Agricultural Research, 2016)
An attempt has been made to compare the input cost and output prices of selected five major crops of Gujarat State i.e. paddy, bajra, cotton (LS), wheat and pigeon pea. The time series data on input cost and output prices were collected from the past reports of "scheme for creating a permanent machinery for studying the cost of cultivation/production of principal crops grown in Gujarat state" (2001 to 2010). The positive and significantly higher growth rate of output prices for all five major crops was observed. The result of the instability index for output prices was found to be low. The high growth and low instability index indicates sustainability in production of these crops, which is the prerequisite for the state. The trend in parity indices shows that the improvement in terms of trade was in favour of farmers in case of paddy, pigeon pea, bajra and cotton crops, which needs to be sustained, where as in case of wheat the parity indices was not much in favour of farmers during the last decade. This clearly indicates that the increase in prices received for output of wheat did not increase in proportion to the increase in prices paid for inputs used in its cultivation.